Across the Board: Runcang Sun on Lignin Nanoparticles. Issue 17 (14th April 2020) - Sun, Runcang
Abstract: In this series of articles, the board members of ChemSusChem discuss recent research articles that they consider of exceptional quality and importance for sustainability. This entry features Prof. R. C. Sun, who highlights the fabrication of lignin nanoparticles and their application in composites, suggesting that further studies and discoveries of the structures and inherent properties of lignin will contribute to extensive and standardized applications of this new green nanomaterial. Abstract : Lignin goes nano : Our board member Prof. Runcang Sun highlights the fabrication of lignin nanoparticles and their application in composites, suggesting that further studies and discoveries of the structures and inherent properties of lignin will contribute to extensive and standardized applications of this new green nanomaterial.